2013
DOI: 10.1111/gcbb.12071
|View full text |Cite
|
Sign up to set email alerts
|

Net land‐atmosphere flows of biogenic carbon related to bioenergy: towards an understanding of systemic feedbacks

Abstract: The notion that biomass combustion is carbon neutral vis-a-vis the atmosphere because carbon released during biomass combustion is absorbed during plant regrowth is inherent in the greenhouse gas accounting rules in many regulations and conventions. But this ‘carbon neutrality’ assumption of bioenergy is an oversimplification that can result in major flaws in emission accounting; it may even result in policies that increase, instead of reduce, overall greenhouse gas emissions. This commentary discusses the sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
41
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 25 publications
0
41
0
3
Order By: Relevance
“…Various recent assessments, in particular of forest-based bioenergy systems, have shown that the emission profiles can range widely depending on the methodological choice of the assessment and included factors. These factors were mainly related to aspects such as type and location of the forests, albedo changes after harvesting, level of climate intensity, harvest frequency, rotation length, conversion technology or type of systemic feedback and direct and indirect impacts [5][6][7][34][35][36]. This and above named factors show the challenges related to natural variability, supply chain and activity characteristics, wider often indirect impacts and methodological choices.…”
Section: Challenges Of the Real Ghg Reduction Potential Of Bioenergy mentioning
confidence: 99%
See 3 more Smart Citations
“…Various recent assessments, in particular of forest-based bioenergy systems, have shown that the emission profiles can range widely depending on the methodological choice of the assessment and included factors. These factors were mainly related to aspects such as type and location of the forests, albedo changes after harvesting, level of climate intensity, harvest frequency, rotation length, conversion technology or type of systemic feedback and direct and indirect impacts [5][6][7][34][35][36]. This and above named factors show the challenges related to natural variability, supply chain and activity characteristics, wider often indirect impacts and methodological choices.…”
Section: Challenges Of the Real Ghg Reduction Potential Of Bioenergy mentioning
confidence: 99%
“…There is usually a significant point source release of GHGs at the point of biomass conversion to energy, predominantly in the form of CO 2 . This release has a global warming potential and affects the dynamics of the climate system in exactly the same way as a unit of CO 2 from fossil fuel combustion [34,36,37].…”
Section: Challenges Of the Real Ghg Reduction Potential Of Bioenergy mentioning
confidence: 99%
See 2 more Smart Citations
“…LCA's major limitation is that it is a static method of analysis that by construction treats biogenic carbon flows as if they are in balance over the defined Blifecycle.^However, that is an incorrect depiction of the situation because biofuel production engages the dynamic flows of the terrestrial carbon cycle (DeCicco 2013;Haberl 2013). Correct analysis must capture the system dynamics and reflect both the time-varying nature of key flows and the initial conditions of the system.…”
mentioning
confidence: 99%